Composite structure
Patent Information
- Application Number
- JP2023142138
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-01
- Publication Date
- 2025-03-13
AI Technical Summary
【0007】 本発明によれば、水硬性組成物の好ましくない特性を克服しつつ好ましい特性をより有効に活用できる複合構造体を提供することができる。
Smart Images

Figure 2025035224000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite structure comprising a hydraulic composition. [Background technology]
[0002] Composite structures in which concrete is combined with other members are known. For example, Patent Document 1 describes a concrete-filled steel pipe structure (CFT structure) in which concrete is filled in a steel pipe. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2022-3216 Summary of the Invention [Problem to be solved by the invention]
[0004] Conventional composite structures, as seen in Patent Document 1, are generally designed to improve bearing capacity and strength. On the other hand, some concretes have excellent properties but also undesirable properties, which limits them in various ways. This problem exists not only for concrete but also for all compositions that have hydraulic properties (hereinafter, these will be referred to as hydraulic compositions).
[0005] An object of the present invention is to provide a composite structure which can overcome undesirable properties of hydraulic compositions while making more effective use of their favorable properties. [Means for solving the problem]
[0006] A composite structure according to one embodiment of the present invention has an outer shell containing cement and a filler material filled in the outer shell, the filler material being a hydraulic composition having a different composition from that of the outer shell. A composite structure according to another embodiment of the present invention has an outer shell made of a metal and a filler filled in the outer shell, the filler being a hydraulic composition, the filler containing Portland cement, and a design standard strength of the filler being 24 N / mm 2 More than 220N / mm 2 The unit weight of Portland cement is 300 kg / m or less. 3 The following is the result. A composite structure according to still another embodiment of the present invention has an outer shell made of a metal and a filling material filled in the outer shell, the filling material being a hydraulic composition, and the design standard strength of the filling material being 80 N / mm 2 That's all. Effect of the Invention
[0007] According to the present invention, it is possible to provide a composite structure that can overcome unfavorable properties of a hydraulic composition while more effectively utilizing favorable properties. [Brief description of the drawings]
[0008] [Figure 1] 1 is a perspective view of a composite structure (pillar member) according to a first embodiment of the present invention. [Diagram 2] 2 is a cross-sectional view of the composite structure shown in FIG. 1. [Diagram 3] FIG. 11 is a cross-sectional view of a composite structure of a comparative example. [Figure 4] FIG. 1 is a diagram showing the relationship between the concrete strength of a filling material and the unit amount of cement. [Diagram 5] FIG. 11 is a perspective view of a composite structure (pillar member) according to a third embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] (First embodiment) FIG. 1 is a partially cutaway perspective view of a composite structure 1 according to a first embodiment of the present invention. Although the composite structure 1 of this embodiment is a column, the use of the composite structure 1 is not limited. The composite structure 1 can be used for columns, beams, slabs, foundation structures, etc. in architectural structures and civil engineering structures. FIG. 2 is a cross-sectional view of the composite structure 1 (column) shown in FIG. 1. FIG. 3(a) is a cross-sectional view of a column 101 (hereinafter referred to as Comparative Example 1) composed only of an outer shell portion 2 described below, and FIG. 3(b) is a cross-sectional view of a column 201 (hereinafter referred to as Comparative Example 2) composed only of a filling material 3 described below.
[0010] The composite structure 1 has an outer shell 2 made of reinforced concrete and a filler material 3 filled in the outer shell 2. The outer shell 2 is a rectangular parallelepiped member having four side parts 6 with openings at the top and bottom, and each side part 6 is embedded with column main reinforcement bars 4 extending in the vertical direction and hoop reinforcement bars 5 extending in the circumferential direction. The outer shell 2 is made of precast concrete, and is fabricated in a factory and then installed on-site, after which the filler material 3 is filled in. Therefore, the outer shell 2 is used as a structural member as well as a formwork for the filler material 3. The entire composite structure 1 may be a precast structure, in which case the filler material 3 is filled in the factory. The outer shell 2 does not need to have reinforcing bars. In this case, it is desirable to place reinforcing bars (column main reinforcement bars 4 and hoop reinforcement bars 5) in the filler material 3. Alternatively, reinforcing bars may be placed in both the outer shell 2 and the filler material 3.
[0011] The shell 2 can be made of general concrete. In this embodiment, Portland cement is used as the cement for the shell 2, and the water-cement ratio can be selected from the range of, for example, 10 to 50%. The composition of the shell 2 is not limited, and can be any composition as long as it contains cement. The shell 2 may be made by a 3D printer.
[0012] Portland cement is commonly used as the cement for concrete. Portland cement is manufactured by burning raw materials such as limestone and clay to produce a mineral called clinker, which is then pre-crushed and finished by adding gypsum. However, since Portland cement emits carbon dioxide during its manufacture (in addition to the carbon dioxide emitted during the generation of energy used in the burning process, carbon dioxide is also emitted from limestone when producing clinker), reducing the amount of Portland cement used is a major challenge from the perspective of reducing carbon dioxide emissions.
[0013] Meanwhile, architectural and civil engineering structures are being required to have longer life spans than ever before. Increasing the strength of concrete (standard design strength, etc.) is an effective way to extend the life span of structures. Figure 4 shows an example of the relationship between concrete strength and the amount (unit amount) of Portland cement used. As can be seen from this figure, it is necessary to increase the unit amount of Portland cement in order to increase concrete strength. For example, according to the Architectural Institute of Japan's "Standard Specifications for Construction Works and Commentary JASS5 Reinforced Concrete Works" (hereinafter referred to as JASS5), in order to meet the "ultra-long" planned service life class, the standard durability design strength of concrete is set at 36 kg / mm 2 The cement that can be used to meet the "ultra-long term" requirement is limited to Portland cement, blast-furnace cement type A, and fly ash cement type A. Although blast-furnace cement type A and fly ash cement type A are types of blended cement, Portland cement accounts for the majority.
[0014] The amount of Portland cement used is roughly proportional to the amount of carbon dioxide emitted. For this reason, in Figure 4, the left vertical axis shows the amount of Portland cement used, while the right vertical axis shows the amount of carbon dioxide emitted when producing a unit volume of concrete. Although it is preferable to use Portland cement to extend the life of a structure, it is difficult to reduce carbon dioxide emissions when the entire structure is made of Portland cement, as in Comparative Example 1.
[0015] For this reason, in this embodiment, the filler 3 is selected so that the relationship between the concrete strength and the unit amount of Portland cement falls within the range surrounded by the thick solid line A in Fig. 4. The filler 3 is composed of a hydraulic composition containing Portland cement and an admixture. The filler 3 has a design standard strength of 24 N / mm 2 More than 220N / mm 2 In the following, the unit weight of Portland cement is 300 kg / m 3 The range surrounded by the thick solid line A includes the filling material 3 that does not contain any Portland cement. Particularly preferably, the filling material 3 has a design standard strength of 36 N / mm 2 More than 60N / mm 2 In the following, the unit weight of Portland cement is 300 kg / m 3 It is selected so that the following is satisfied (the range surrounded by the thick dashed line B in Figure 4).
[0016] The design standard strength has a margin for the actual compressive strength. Based on the actual strength, the compressive strength of the filling material 3 is preferably, for example, 30 N / mm 2 More than 250N / mm 2 Particularly preferably, the compressive strength is, for example, 40 N / mm 2 More than 80N / mm 2 The unit weight of Portland cement is 300 kg / m 3 It is selected within the following range:
[0017] By using such a hydraulic composition as the filling material 3, it is possible to reduce the amount of carbon dioxide emitted. 2 , Portland cement unit weight is 300 kg / m 3 When filling material 3 is made of concrete (P1 in the figure), the carbon dioxide emissions are 240 kg / m 3 In contrast, the design strength is 60N / mm 2 If the filler 3 is made up of only Portland cement, the carbon dioxide emissions will be 440 kg / mm 2(P2 in the figure) In other words, by using the filler 3 of this embodiment, the amount of carbon dioxide emitted in the manufacturing process of the filler 3 can be reduced by almost half.
[0018] As the hydraulic composition used for the filling material 3, for example, blast furnace cement type B or type C specified in the Japanese Industrial Standard JIS R 5211:2009 "Blast Furnace Cement" can be used. Blast furnace cement type B contains ground granulated blast furnace slag at a mass ratio of more than 30% and not more than 60%, and blast furnace cement type C contains ground granulated blast furnace slag at a mass ratio of more than 60% and not more than 70%. The filling material 3 can also be composed of a hydraulic composition in which the mass ratio of ground granulated blast furnace slag is increased to 70% or more. Alternatively, fly ash cement type B or type C specified in the Japanese Industrial Standard JIS R 5213:2009 "Fly ash cement" can be used as the hydraulic composition. Fly ash cement type B contains fly ash at a mass ratio of more than 10% and not more than 20%, and fly ash cement type C contains fly ash at a mass ratio of more than 20% and not more than 30%. The middle filling material 3 may be made of a hydraulic composition in which the mass ratio of fly ash is increased to 30% or more. Alternatively, a hydraulic composition that does not contain Portland cement may be used as the middle filling material 3.
[0019] Since the amount of carbon dioxide generated during production of ground granulated blast furnace slag and fly ash is almost negligible, they are effective in reducing carbon dioxide emissions. In the following explanation, concrete with a low mass ratio of cement, such as blast furnace cement type B, type C, fly ash cement type B, and type C Portland, is called low-carbon concrete. Low-carbon concrete is also concrete with a high mass ratio of admixtures such as ground granulated blast furnace slag and fly ash.
[0020] Blast-furnace cement type B, C, fly ash cement type B, and C cannot be used to satisfy the "ultra-long term" requirement in the above-mentioned JASS5. In other words, the entire structure cannot be made of any of blast-furnace cement type B, C, fly ash cement type B, or C, as in Comparative Example 2. One of the reasons is the neutralization of concrete. When neutralization occurs, the passive film on the surface of the reinforcing bar becomes unstable, making the reinforcing bar more susceptible to corrosion. In general, low-carbon concrete is prone to neutralization due to its low alkalinity. However, the concrete involved in neutralization is the concrete in the covering part of the reinforcing bar, and in this embodiment, this range is the outer shell part 2, so neutralization is less likely to occur.
[0021] Furthermore, if the entire structure is made of low-carbon concrete as in Comparative Example 2, it is necessary to make the rebar cover larger to prevent corrosion of the rebar due to carbonation, which tends to lead to an increase in the cross section of the structure. In this embodiment, the shell 2 can be made of concrete mainly made of Portland cement, so a large cover is not required. Therefore, the composite structure 1 of this embodiment can at least avoid a significant increase in size compared to Comparative Example 2.
[0022] In this manner, in this embodiment, carbon dioxide emissions are reduced by providing the inner filling material 3, which contains less unit amount of Portland cement than the outer shell 2. At the same time, by providing the outer shell 2 mainly made of Portland cement, the life span of the composite structure 1 is extended and size increase is suppressed. It is preferable that the outer shell 2 satisfies the performance stipulated in the Architectural Institute of Japan's "Guidelines for the Design and Construction of High-Durability Reinforced Concrete Structures, 1991." In addition, to satisfy the "ultra-long term" requirement of JASS5, the design standard strength of the outer shell 2 is 36 N / mm 2 It is preferable that the amount is equal to or more than that.
[0023] Furthermore, the composite structure 1 of this embodiment has the following effects. First, since low-carbon concrete develops strength slowly, it is necessary to delay the removal of the formwork in Comparative Example 2. Also, low-carbon concrete requires a longer period of moist curing. These factors increase the construction period. However, since this embodiment is configured to cover the inner filling material 3 with the outer shell 2, there is no need to remove the formwork and moist curing. Also, since drying can be prevented, the occurrence of cracks caused by drying shrinkage can be suppressed.
[0024] On the other hand, in order to suppress the neutralization of concrete, it is also effective to use high-strength concrete. However, when the strength of concrete is increased, cracks are more likely to occur on the surface of the structure where bending compression acts. In order to suppress cracks, it is effective to add fibers to the concrete. When the structure is made of a single concrete as in Comparative Examples 1 and 2 (when the concrete of the structure is poured all at once), the fibers are distributed throughout the structure. In other words, the fibers are mixed into the inside of the structure where they are not necessary to suppress cracks, and the amount of fibers increases, making it uneconomical. In this embodiment, it is only necessary to add fibers to the outer shell part 2, so the amount of fibers is reduced and costs can be suppressed.
[0025] In addition, in a relatively large structure, the orientation of the fibers is three-dimensional and random. The fibers that can be expected to have a crack suppression effect are mainly parallel to the surface of the structure, and the fibers that run from the surface to the center of the structure cannot be expected to have much of a crack suppression effect. On the other hand, in the case of a relatively thin plate-like structure such as the outer shell 2, the orientation of the fibers is two-dimensional and tends to be aligned parallel to the outer surface of the structure. Therefore, in the outer shell 2, the amount of fibers oriented in the thickness direction of the outer shell 2 decreases and the amount of fibers oriented parallel to the outer surface increases, making it possible to increase the crack prevention effect with a small amount of fibers.
[0026] Second embodiment In this embodiment, the configuration of the composite structure 1 is the same as that of the first embodiment, but the design standard strength of the filling material 3 is 80 N / mm 2 The design standard strength of the outer shell 2 is 80N / mm2 In the following explanation, the design strength is 80N / mm 2 The above concrete is called ultra-high strength concrete. Ultra-high strength concrete is manufactured by using specific cement, silica fume, aggregate, etc., and adding expansive agents and shrinkage reducing agents appropriately. In general, ultra-high strength concrete has high strength, but is inferior in heat resistance and fire resistance, and is more likely to explode due to heat during a fire, for example, than ordinary concrete. When the concrete covering the reinforcing bar explodes, the reinforcing bar is heated, and there is a possibility that structural strength will be impaired due to loss of the concrete cross section and a decrease in the strength of the reinforcing bar due to heating. Since the outer shell 2 can be made of concrete with a lower strength than the filling material 3, the possibility of explosion is relatively low. Therefore, the composite structure 1 of this embodiment can achieve both high strength and heat resistance and fire resistance. Based on the actual strength, the compressive strength of the filling material 3 is, for example, 100 N / mm 2 The compressive strength of the outer shell 2 is, for example, 100 N / mm 2 In the present embodiment as well, the filling material 3 may or may not contain Portland cement.
[0027] (Third embodiment) FIG. 5 is a partially cutaway perspective view of a composite structure 1 according to a third embodiment of the present invention. In this embodiment, the composite structure 1 has an outer shell 6 made of metal, and a filler material 3 filled in the outer shell 6. The metal is typically iron, but is not limited to iron. The filler material 3 may be the same as the hydraulic composition used in the first or second embodiment. That is, in one example, the hydraulic composition includes Portland cement and an admixture, and the design standard strength of the hydraulic composition is 24 N / mm 2 More than 220N / mm 2 The unit weight of Portland cement is 300 kg / m or less. 3 Based on the actual strength, the compressive strength of the hydraulic composition is preferably, for example, 30 N / mm 2 More than 250N / mm 2 Particularly preferably, the compressive strength is, for example, 40 N / mm 2 More than 80N / mm 2The unit weight of Portland cement is 300 kg / m 3 In another example, the design strength of the hydraulic composition is selected within the range of 80 N / mm 2 The above is the case. Based on the actual strength, the compressive strength of the hydraulic composition is, for example, 100 N / mm 2 That is all. In this embodiment as well, the filling material 3 may or may not contain Portland cement.
[0028] Although the present invention has been described above with reference to several embodiments, the present invention is not limited to these embodiments. The composite structure 1 of this embodiment is a concrete structure, but at least one of the outer shell 2 and the filling material 3 may be a mortar structure that does not contain coarse aggregate. The filling material 3 may be lightweight concrete. [Explanation of symbols]
[0029] 1 Composite structure 2,6 Outer shell 3 Filling material
Claims
1. The present invention has an outer shell portion containing cement and a filling material filled in the outer shell portion, The composite structure has a filling material which is a hydraulic composition having a different composition from that of the outer shell.
2. The design standard strength of the filling material is 24 N / mm 2 Above, 220N / mm 2 2. The composite structure of claim 1 , wherein:
3. The compressive strength of the filling material is 30 N / mm 2 Above, 250N / mm 2 2. The composite structure of claim 1 , wherein:
4. The filling material contains Portland cement, and the unit amount of the Portland cement is 300 kg / m 3 3. The composite structure of claim 2, wherein:
5. 5. The composite structure of claim 4, wherein the fill material is blast furnace cement type B or type C.
6. 5. The composite structure of claim 4, wherein said filler is fly ash cement type B or type C.
7. 2. The composite structure of claim 1, wherein said shell and said filler comprise Portland cement, and wherein a unit amount of said Portland cement in said filler is less than a unit amount of said Portland cement in said shell.
8. 10. The composite structure of claim 1, wherein said fill material is free of Portland cement.
9. The design standard strength of the filling material is 80 N / mm 2 or more, and the design standard strength of the outer shell portion is 80 N / mm 2 10. The composite structure of claim 1 , wherein the thickness of the composite structure is less than 100 μm.
10. The compressive strength of the filling material is 100 N / mm 2 or more, and the compressive strength of the outer shell portion is 100 N / mm 2 10. The composite structure of claim 1 , wherein the thickness of the composite structure is less than 100 μm.
11. 10. The composite structure of claim 9, wherein only the outer shell is loaded with fiber.
12. The container has an outer shell made of metal and a filling material filled in the outer shell, The filling material is a hydraulic composition, The design standard strength of the filling material is 24 N / mm 2 Above, 220N / mm 2 A composite structure that is:
13. The container has an outer shell made of metal and a filling material filled in the outer shell, The filling material is a hydraulic composition, The compressive strength of the filling material is 30 N / mm 2 Above, 250N / mm 2 A composite structure that is:
14. The filling material contains Portland cement, and the unit amount of the Portland cement is 300 kg / m 3 13. The composite structure of claim 12, wherein:
15. 15. A composite structure as claimed in any one of claims 1 to 14, wherein the shell is made of precast concrete.
16. The container has an outer shell made of metal and a filling material filled in the outer shell, The filling material is a hydraulic composition, The design standard strength of the filling material is 80 N / mm 2 A composite structure that is the above.
17. The container has an outer shell made of metal and a filling material filled in the outer shell, The filling material is a hydraulic composition, The compressive strength of the filling material is 100 N / mm 2 A composite structure that is the above.
Citation Information
Patent Citations
Concrete filling steel pipe pole
JP2022003216A